2018
DOI: 10.1016/j.devcel.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Orchestrates Cell Polarity to Promote Embryonic Wound Healing

Abstract: Graphical AbstractHighlights d Wound-induced ROS production promotes healing in Drosophila and zebrafish embryos d ROS direct redistribution of junctions and the cytoskeleton at the wound margin d Src oxidation contributes to E-cadherin and myosin polarization around wounds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 61 publications
6
67
0
Order By: Relevance
“…Intracellular ROS Contributes to the Activation of Macrophages An increase in TCFB probe fluorescence was observed within hemocytes that were close to the wound site (Figures 2A and 2A 0 ). It has previously been demonstrated that ROS levels increase in the epithelia around a wound in both Drosophila and zebrafish embryos (Hunter et al, 2018). Appropriate levels of ROS in tissues are maintained by a series of enzymes, including superoxide dismutase (Sod) and catalase (Nordberg and Arné r, 2001).…”
Section: Injury-induced Ros Burst Is Essential For Upd-3 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular ROS Contributes to the Activation of Macrophages An increase in TCFB probe fluorescence was observed within hemocytes that were close to the wound site (Figures 2A and 2A 0 ). It has previously been demonstrated that ROS levels increase in the epithelia around a wound in both Drosophila and zebrafish embryos (Hunter et al, 2018). Appropriate levels of ROS in tissues are maintained by a series of enzymes, including superoxide dismutase (Sod) and catalase (Nordberg and Arné r, 2001).…”
Section: Injury-induced Ros Burst Is Essential For Upd-3 Expressionmentioning
confidence: 99%
“…The migration of embryonic hemocytes to sites of damage where H 2 O 2 is produced is regulated by the apoptotic receptor Draper (drpr), together with the Src family kinase Src42A and a Syk homolog, Shark ( Figure S4A) (Evans et al, 2015). H 2 O 2 drives wound closure through Src42A, which promotes polarization of junctions and cytoskeleton around wounds (Hunter et al, 2018). A previous study demonstrated that homozygous drpr D5 adults have reduced longevity (Draper et al, 2014).…”
Section: Induction Of Upd-3 Is Dependent On the Src42a/shark/ Draper mentioning
confidence: 99%
“…In particular, Ca 2+ diminished ROS from ROS generation sites within the mitochondria under normal conditions and enhanced ROS generation when generation sites were inhibited by pharmacological agents . Further, quantitative in vivo microscopy in Drosophila and zebrafish embryos identified ROS as crucial signals that regulate cell polarity after wounding . Hunter et al utilized fluorescent imaging after wounding Drosophila embryos and demonstrated Ca 2+ ‐dependent mitochondrial ROS production correlates with the site of actomyosin cable assembly.…”
Section: Feedback From Physiological Signaling Ensures Robustness Of mentioning
confidence: 99%
“…103 Further, quantitative in vivo microscopy in Drosophila and zebrafish embryos identified ROS as crucial signals that regulate cell polarity after wounding. 104 Hunter et al utilized fluorescent imaging after wounding Drosophila embryos and demonstrated Ca 2+ -dependent mitochondrial ROS production correlates with the site of actomyosin cable assembly. This suggests that wound-induced ROS production promotes healing in Drosophila and zebrafish embryos.…”
Section: Feedback From Physiological Signaling Ensures Robustness Omentioning
confidence: 99%
“…Recent studies have addressed the role of mitochondria in tissue repair, showing that mitochondrial reactive oxygen species (ROS) promote wound healing by regulating F-actin and Myosin at the wound edge, either by acting on Rho GTPases (Muliyil and Narasimha, 2014; Xu and Chisholm, 2014) or on cell-cell junction remodeling (Hunter et al, 2018). In this work, we show that the mitochondrial dynamics machinery is required for repair, as mutants for these proteins fail to close epithelial wounds.…”
Section: Introductionmentioning
confidence: 99%